PEMANFAATAN MEDIA PEMBELAJARAN DIGITAL DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK SDIT MUTIARA MIFTAHUL JANNAH - Silpa; Pratama, Riki Adi; Karima, Syifaul; Sulastri; Mustofa, Ihsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT The rapid advancement of digital technology has significantly influenced educational practices, particularly in primary education. This study aims to explore the utilization of digital learning media in enhancing students’ learning motivation at SDIT Mutiara Miftahul Jannah. The research employed a qualitative descriptive method to obtain an in-depth understanding of teachers' and students' experiences regarding digital media implementation in classroom learning. Data were collected through classroom observations, semi-structured interviews with teachers and students, and documentation analysis. The findings indicate that the integration of digital learning media—such as interactive presentation slides, educational videos, online learning platforms, and gamified applications—has positively influenced students’ motivation by increasing engagement, curiosity, active participation, and enjoyment in learning activities. Students demonstrated higher levels of enthusiasm and attentiveness during digital-based instruction compared to conventional teaching methods. However, several challenges were identified, including limited technological facilities, inconsistent internet connectivity, and varying levels of digital literacy among students. The study concludes that digital learning media, when implemented strategically and supported by adequate infrastructure and teacher competence, can significantly enhance students’ learning motivation and contribute to a more dynamic and student-centered learning environment in primary schools.